Modern management in the global mining industry - Adams, Robin G.; Gilbert, Christopher L.; Stobart, Christopher G. (Emerald Publishing Limited, 2019)
The mining industry faces distinct challenges. Mines have long lives, companies have little control over the prices at which they sell, prices are volatile, and the environmental impacts of mining are often not well managed. Despite this, the mining industry has received relatively little attention from neither economists nor the wider business community. There is a need to address the unique management challenges raised by this globally important industry.Modern Management in the Global Mining Industry addresses the economics of mining industries and the management of global mining companies in a manner which is both practical and guided by economic and management theory. Leading with the assertion that mining generates substantial benefits for all its stakeholders provided it is well-managed, and that this includes management of environmental impacts, the book argues that mining companies should move to seeing environmental preservation and sustenance of local communities as an objective rather than a constraint. The book will be an important reference for practitioners working in mining and related industries and to researchers of economic and management theory, mining operations, mining engineering and commodities.